2016
DOI: 10.1016/j.jsv.2016.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Internal resonances and dynamic responses in equivalent mechanical model of partially liquid-filled vessel

Abstract: The paper treats oscillations of a liquid in partially filled vessel under horizontal harmonic ground excitation. Such excitation may lead to hydraulic impacts. The liquid sloshing mass is modeled by equivalent pendulum, which can impact the vessel walls. We use parameters of the equivalent pendulum for well-explored case of cylindrical vessels. The hydraulic impacts are modeled by high-power potential function. Conditions for internal resonances are presented. A non-resonant behavior and dynamic response rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…On the other hand, it has been observed that if the sloshing is relatively mild, the free surface does not break and the sloshing motion is not chaotic [16], and its motion pattern is analogous to a mechanical system. erefore, many past studies simplify the sloshing liquid into a spring-mass [17,18] or a pendulum [19,20] system. e complication encountered in this approach is that since the mechanical analogy is not based on the fluid theory, it is hard to derive the parameters (mass, stiffness, damping, and natural frequency) of the analogical model directly, unless the tank geometry is simple such as a rectangular tank.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been observed that if the sloshing is relatively mild, the free surface does not break and the sloshing motion is not chaotic [16], and its motion pattern is analogous to a mechanical system. erefore, many past studies simplify the sloshing liquid into a spring-mass [17,18] or a pendulum [19,20] system. e complication encountered in this approach is that since the mechanical analogy is not based on the fluid theory, it is hard to derive the parameters (mass, stiffness, damping, and natural frequency) of the analogical model directly, unless the tank geometry is simple such as a rectangular tank.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic jumps and wave collisions with the vessel shells express the strong non-linearities in the system [7]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Equivalent mechanical models for linear small-amplitude sloshing were based on pendulums and mass-spring systems were studied for different excitations and tank shapes [1], [38], [39]. However, since nonlinear sloshing regimes cannot be described by the linear models, major attempts were made to formulate nonlinear reduced order equivalent mechanical models [7], [8], [10], [26], [40], [41] that may predict and describe nonlinear responses observed experimentally. For instance, nonlinear rotary sloshing in a scale model of Centaur propellant tank at low fill level was modeled by combination of ordinary linear pendulum and a spherical pendulum (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaneko and Yoshida (1999) and Kaneko and Mizota (2000) presented an analytical model describing the effectiveness of deep-water types of rectangular and cylindrical TLDs (DTLDs) with a submerged net for reducing the horizontal vibration of the structural system. Other studies examined the dynamic behavior of a liquid impact of a tank using as an equivalent inverted pendulum or a mass-spring-damper (Pilipchuk and Ibrahim, 2000; Farid and Gendelman, 2016; Farid et al., 2017).…”
Section: Introductionmentioning
confidence: 99%